Disorders of neural crest derivates in oncoradiological practice - Papp, Tamas; Ferenczi, Zsuzsanna; Petro, Matyas; Meszar, Zoltan; Kepes, Zita; Berenyi, Ervin (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Hundreds of articles discuss the imaging characteristics and molecular background of prominent gastrointestinal (GI) motility disorders and tumors of the peripheral nervous system, but according to our knowledge an article focusing on the classification and developmental background of these heterogeneous diseases is not to be found. Our aim is to give insight on the common features of several diseases and tumors, starting with their common source of origin, the neural crest (NC). The NC is a transient cell population of the embryo, which differentiates into several organs/structures of our body (sympathetic trunk, adrenal medulla). Although the incidence of the individual tumors of NC cells is not high by themselves, the summation of these incidences may be relevant in the daily routine. In the introduction we mention the most prominent developmental routes and molecular pathways of NC cells, which is crucial to understand the pathogenesis and the wide range of involved cell types from the colon to the adrenal gland. We summarized the most important, useful pathological findings and imaging techniques from the X-ray to the positron emission tomography—computed tomography (CT) in order to help the identification of these diseases. This article may help to better understand NC lineage and its unique, diverse role during ontogeny, which may influence the radiologists to change several convictions, or understand better the background and/or connections of a wide range of tumors and syndromes.